Is Theory Guiding Our Work? A Scoping Review on the Use of Implementation Theories, Frameworks, and Models to Bring Community Health Workers into Health Care Settings. Issue 6 (November 2019) - Allen, Caitlin G.; Barbero, Colleen; Shantharam, Sharada; Moeti, Refilwe
Abstract : Community health workers (CHWs) are becoming a well-recognized workforce to help reduce health disparities and improve health equity. Although evidence demonstrates the value of engaging CHWs in health care teams, there is a need to describe best practices for integrating CHWs into US health care settings. The use of existing health promotion and implementation theories could guide the research and implementation of health interventions conducted by CHWs. We conducted a standard 5-step scoping review plus stakeholder engagement to provide insight into this topic. Using PubMed, EMBASE, and Web of Science, we identified CHW intervention studies in health care settings published between 2000 and 2017. Studies were abstracted by 2 researchers for characteristics and reported use of theory. Our final review included 50 articles published between January 2000 and April 2017. Few studies used implementation theories to understand the facilitators and barriers to CHW integration. Those studies that incorporated implementation theories used RE-AIM, intervention mapping, cultural tailoring, PRECEDE-PROCEED, and the diffusion of innovation. Although most studies did not report using implementation theories, some constructs of implementation such as fidelity or perceived benefits were assessed. In addition, studies that reported intervention development often cited specific theories, such as the transtheoretical or health belief model, that helped facilitate the development of their program. Our results are consistent with other literature describing poor uptake and use of implementation theory. Further translation of implementation theories for CHW integration is recommended. Abstract : Supplemental Digital Content is Available in the Text.